(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
Groundwater is a reserve and strategic reservoir of stored fresh water، It is the most important source of drinking water in many countries of the world. Groundwater is exposed to many pollutants from a various sources. The most important of these sources are pollutants from agricultural and urban activities، which are now a global problem. The research aims to study many physical and chemical properties of groundwater in Jableh plain in Lattakia, by collecting samples of groundwater from the study area and measuring a number of physical and chemical parameters (temperature، turbidity، electrical conductivity ، pH ، fluoride، chloride، nitrates، nitrite and sulphates (.The results showed that temperature، conductivity، pH were within the allowed limits according to Syrian standards for drinking water. In contrast، the concentrations of some ions exceeded the allowed limits، such as nitrates,which it’s concentration is up to 177mg / l، Indicating that there are many factors cause contamination of these water sources with nitrate .